Frações e qualidade da matéria orgânica de um solo construído vegetado com gramíneas após a mineração de carvão. - Leal, Otávio dos Anjos (2011)
After the coal mining is necessary the topographic reconstruction of the area, origining constructed soils, which typically has low soil organic matter stocks (SOM). The cover crops can help to restore these stocks, improving constructed soil conditions. The aim of this study was to evaluate the effect of cover crops on the total organic carbon stocks (TOC), carbon in organic matter fractions and the organic matter quality of a soil constructed after the coal mining. Two experiments were evaluated in a constructed soil in Candiota/RS, one with six years (E6), and another with two years (E2). The treatments were cover crops: Limpograss (T1), Pensacola (T2), Tifton Grass (T3) and Brachiaria Brizantha (T4), in E6 and T1 - Vaqueiro, T2 - Brachiaria Brizantha, T3 - Tanzania, T4 - Brachiaria Humidicola T5 - Limpograss, T6 Tifton Grass, in E2. In these treatments, were collected samples in the layer from 0.00 to 0.03 m of soil. For comparison, were collected in adjacent areas, samples from a constructed soil without vegetation (T8) and samples from a natural soil (Ultisol) with native vegetation (T9). In E6 were made the chemical and physical (grain size and densimetric) fractionations of SOM, determining the total nitrogen stocks (TN), TOC and carbon fractions, analysis of Fourier transform infrared (FTIR) of humic acid (HA) and laser induced fluorescence (LIF) of whole soil. It were calculated HA percentage (HI), ratio AH/fulvic acid (HR), the carbon management index (CMI) and the humification degree of SOM (HLIF). In E2, were made the same analysis, except for chemical fractionation. In E6 the higher HA stock was observed in T4, which did not differ from T1. The same occurred in the free light fraction (FLF) and in the occluded light fraction (OLF). The HR ranged from 0.27 to 1.0 and treatments with higher HI were T1 and T4, indicating a more humified SOM. According to FTIR analysis, the HA of T1, T2 and T4 resembled the T9, while the T3 resembled the T8. The constructed soil quality was improved mainly by T1 and T4, which had the highest CMIs. Compared to T8, the plants increased the TOC, TN, carbon in organic matter fractions and CMI, however, these values were lower than those at T9. In E2, the TOC stocks did not differ between treatments, and the higher NT stock was observed in T3, not differing from T2. The T2 and T3 presented the highest carbon stocks in the free light and coarse fractions and the highest CMIs. The plants increased the TOC, NT, carbon in organic matter fractions and the CMI in comparison to T8. In both experiments, the HLIF from the treatments was highest than the T9 and smallest than T8 and independent of plant specie there was partial restore of soil quality. The species most recommended to restore the degraded areas were Limpograss and Brachiaria Brizantha in E6 and Tanzania and Brachiaria Brizantha in E2.